Chemical composition, sources and evolution of wintertime inorganic and organic aerosols in urban Shanghai, China - Qian, Yijie; Cai, Dongmei; Zhang, Miaomiao; Huang, Xiaojuan; Huo, Juntao; Duan, Yusen; Cheng, Tiantao (Frontiers in Environmental Science, 2023)
China experienced severe haze pollution in the past decades. However, systematic characterization of atmospheric fine particles with advanced measurement techniques has been very scarce in Shanghai, which is the largest megacity in China. Herein, we present the characterization of non-refractory submicron aerosol (NR-PM1) in urban Shanghai during winter 2017 by applying an Aerosol Chemical Speciation Monitor (ACSM, Aerodyne Research Inc.). The NR-PM1 is predominated by organics (43%), followed by nitrate (29%), sulfate (18%), ammonium (7%) and chloride (3%). Regarding the OA factors, three OA factors were identified and classified as HOA, LO-OOA, and MO-OOA, which contributed 32%, 22% and 46% to total OA respectively. The NR-PM1 composition exhibited an increase in SIA (sulfate, nitrate and ammonium) contribution from clean episodes (49%) to pollution episodes (59%), while OA contribution decreased accordingly from 48% to 39%. The strong increase of sulfate in high-RH pollution episodes indicated that aqueous-phase oxidation of SO2 could be an important formation process for sulfate during particulate air pollution period. The contribution of nitrate was elevated from 25% during clean episodes to 32% during polluted episodes, likely owing to the increase of RH which facilitates the hydrolysis of N2O5 and the gas-to-particle partitioning of hydrophilic NH4NO3 and. Further analysis of atmospheric formation relevance suggested that LO-OOA formation was mainly driven by aqueous-phase chemistry reactions, whereas photochemical oxidation became an important process for MO-OOA formation. Meanwhile, LO-OOA formation may also be influenced by atmospheric oxidative tracer (i.e., Ox), as LO-OOA exhibited a distinct peak at noon under high-RH condition.